1976
DOI: 10.1177/001391657682006
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Illness Complaints and Degree of Crowding in a Prison Environment

Abstract: Illness complaint rates were examined in relation to degree of crowding in a federal prison and a county jail. It was found that dorm inmates in the prison had higher complaint rates than those in single cells. In the jail inmates in units of high spatial and social density had higher complaint rates than those in less crowded units. These findings suggest that crowding in prisons may induce psychological stress which can be reflected in an increased level of illness complaints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 9 publications
2
35
1
Order By: Relevance
“…Among other things, we know from early research that prison overcrowding increases negative affect among prisoners (e.g., Paulus, Cox, McCain, & Chandler, 1975), elevates their blood pressure (e.g., D'Atri, 1975), and leads to greater numbers of prisoner illness complaints (e.g., McCain et al, 1976). Moreover, exposure to "long-term, intense, inescapable crowding" of the sort that characterizes many prison environments results in high levels of stress that "can lead to physical and psychological impairment" (Paulus, McCain, & Cox, 1978, p. 115;see, also, Ostfeld, Kasl, D'Atri, & Fitzgerald, 1987).…”
Section: Overcrowding: More Prisoners Than Can Be Safely and Humanelymentioning
confidence: 99%
“…Among other things, we know from early research that prison overcrowding increases negative affect among prisoners (e.g., Paulus, Cox, McCain, & Chandler, 1975), elevates their blood pressure (e.g., D'Atri, 1975), and leads to greater numbers of prisoner illness complaints (e.g., McCain et al, 1976). Moreover, exposure to "long-term, intense, inescapable crowding" of the sort that characterizes many prison environments results in high levels of stress that "can lead to physical and psychological impairment" (Paulus, McCain, & Cox, 1978, p. 115;see, also, Ostfeld, Kasl, D'Atri, & Fitzgerald, 1987).…”
Section: Overcrowding: More Prisoners Than Can Be Safely and Humanelymentioning
confidence: 99%
“…Other investigators have recently studied crowding in the prison environment using similar methods. Paulus and coworkers have observed that inmates in dormitories had more negative affect, illness complaints, and higher BP than prisoners in cells (31)(32)(33). Megargee has noted that high density w*b associated with high rates of rhlscflttdilrt in correctional institutions (34).…”
mentioning
confidence: 99%
“…Elevated levels of mental and physical illness have been shown to result from certain types of crowding and particular individuals may find it especially difficult to cope with crowded conditions (McCain, et al, 1976;Toch, 1977;see 1'hornberry and Call, 1983, for a literature review).…”
Section: Causes and Consequences Of Prison Overcrowdingmentioning
confidence: 99%